2012
DOI: 10.1039/c2jm16453a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of photoactive ZnGeP2 nanowire films

Abstract: Photoactive ZnGeP 2 nanowires have been prepared by solid-source sublimation chemical vapor deposition using Sn catalysts. Nanowire films with areas >0.5 cm 2 on Si(100) and Si(111) substrates were deposited with variable nanowire length and diameter. Transmission electron microscopy (TEM), scanning TEM (STEM), and polarized Raman microscopy indicated nanowires exhibited single-crystal character and compositional homogeneity. Photoelectrochemical measurements performed in an aqueous electrolyte indicated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…group III-V, II-VI, IV-VI) and ternary compounds have been synthesized. 4,[19][20][21][22][23][24][25][26] The macroscopic optoelectronic and electrochemical properties of such wire arrays have been experimentally characterized [27][28][29][30][31] , but nanoscale analyses that aim to provide a microscopic understanding of these properties have been mostly limited to theoretical and computational methodologies. [32][33][34][35] The optical excitation of photoactive semiconductor substrates immersed in a metal-ion solution can provide the driving force for deposition of a metal.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
See 1 more Smart Citation
“…group III-V, II-VI, IV-VI) and ternary compounds have been synthesized. 4,[19][20][21][22][23][24][25][26] The macroscopic optoelectronic and electrochemical properties of such wire arrays have been experimentally characterized [27][28][29][30][31] , but nanoscale analyses that aim to provide a microscopic understanding of these properties have been mostly limited to theoretical and computational methodologies. [32][33][34][35] The optical excitation of photoactive semiconductor substrates immersed in a metal-ion solution can provide the driving force for deposition of a metal.…”
Section: Table Of Contents (Toc) Graphicmentioning
confidence: 99%
“…Semiconductor mesostructures have been studied extensively due to their unique band gap energies, absorption and reflectance properties, charge-transport pathways, and increased surface area, relative to their planar counterparts. The ability to tailor such properties has made mesostructures attractive architectures for applications in areas including photonics, photovoltaics, electronics, , catalysis, and sensing. , Mesostructured semiconducting wire arrays composed of elemental, binary compounds (e.g., group III–V, II–VI, IV–VI) and ternary compounds have been synthesized. , The macroscopic optoelectronic and electrochemical properties of such wire arrays have been experimentally characterized, but nanoscale analyses that aim to provide a microscopic understanding of these properties have been mostly limited to theoretical and computational methodologies. …”
mentioning
confidence: 99%
“…A clear F 1s signal in the high-resolution XP spectra after reaction of GaP(111)B with o -CF 3 C 6 H 4 CH 2 SO 2 Cl indicated that this strategy was viable (Table ). A functionalized , form of Coomassie Blue dye featuring a terminal sulfonyl chloride was reacted with freshly etched p-GaP(111)B in methanol for 1 h at 55 °C in the glovebox. XP spectra following functionalization showed evidence of surface-bound Coomassie Blue (Supporting Information, Figure S9), with a monolayer coverage of 0.69.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, surface atop P atoms with one available bonding orbital (as featured on GaP(111)B and InP(111)B) on these materials should also be reactive toward organic halides. Such surface chemistry may benefit the use of these materials in electrical/electrochemical technologies, as each of these materials has been explored as the light harvesting component in solar cell designs. ,, Since surface defects and corrosion/oxidation at the interfaces of the light harvesting component are detrimental to energy conversion/storage efficiencies, chemical methods that can ameliorate such problems have value. The data presented here represent one new possible approach for phosphides in these applications.…”
Section: Discussionmentioning
confidence: 99%
“…Ni 2 P, Ni 3 P, Ni 5 P 2 , Ni 8 P 3 and Ni 12 P 5 ), and broad applications in the field of catalysis. 15,16 To prepare Ni x P y with various shapes and sizes, many methods have been developed, including organic precursor decomposition, 17,18 chemical vapor deposition, 19,20 solid phase reaction, 21,22 temperature-programmed hydrogen-reduction route, [23][24][25] and hydrothermal or solvothermal technique 26,27 etc. In 2007, Henkes 28 and Chiang 29 respectively obtained Ni 2 P nanoparticles and hollow Ni 2 P nanospheres through direct reaction between freshly formed Ni nanocrystals and trioctylphosphine (TOP).…”
Section: Introductionmentioning
confidence: 99%